Clinical Identification and Characteristic Analysis of Giant Cell Myocarditis in 12 Cases - Liu, Shangyu; Zheng, Lihui; Shen, Lishui; Wu, Lingmin; Yao, Yan (Frontiers in Cardiovascular Medicine, 2021)
Aims: Giant cell myocarditis (GCM) is a rare, rapidly progressing cardiomyopathy with high mortality, if not diagnosed and treated in time. We analyzed the progression and clinical manifestations of patients with definitive diagnosis of GCM. Methods and Result: We enrolled 12 patients diagnosed with GCM in the explanted heart during heart transplantation (HTx) or by endomyocardial biopsy (EMB) and collected information on demographic data, cardiac structure and function, arrhythmias, preliminary diagnosis, and delay of the diagnosis. Seven cases were diagnosed from biopsy samples during HTx, and five cases were diagnosed through EMB. Before the diagnosis of GCM based on pathological analysis, these patients had been incorrectly diagnosed with arrhythmogenic right ventricular cardiomyopathy (n = 5), dilated cardiomyopathy (n = 2), ventricular tachycardia (n = 2), viral myocarditis (n = 1), cardiac amyloidosis (n = 1), and ischemic cardiomyopathy (n = 1) based on clues such as symptoms, arrhythmia, and cardiac imaging. Patients diagnosed with GCM through EMB had a shorter symptom-onset-to-diagnosis time (6.6 ± 2.7 months) and milder heart damage (left ventricular ejection fraction, 47.2 ± 8.8%) than those diagnosed during HTx (11.0 ± 3.3 months, P = 0.034; 31.4 ± 10.9%, P = 0.024). Conclusion: GCM is easily misdiagnosed as other types of myocarditis and cardiomyopathy. Pathological examination of the myocardium is the most reliable diagnostic method for GCM. Endocardial biopsy can identify patients with GCM at an earlier stage.